Comparison of Cytotoxicity effects of propionic acid compounds to THLE-2 and HEP-G2 cells - Hakim, Muhammad Nazrul; Hong, Mak Jun; Keong, Yong Yoke; Ahmad, Zuraini (Science Alert, 2024)
Background and Objective: The nonsteriodal anti-inflammatory drugs (NSAIDs) are mainly used for analgesia, anti-pyretic, and for reducing swelling. NSAIDs are one of the most widely prescribed medication worldwide, however with many adverse drug reactions such as gastrointestinal disturbances, liver and kidney toxicity. The current study accessed the cyto-effects of 2-(4-(2-methylpropyl)phenyl)propanoic acid (Ibuprofen/2-4-2MPPPA) and 2 other propionic acid derivatives 3-(4-Hydroxyphenyl)propionic acid (3-4HPPA) and 3-(4-Aminophenyl)propionic Materials and Methods: HepG2 cells and THLE-2 cells were incubated with 100, 50, 25, 12.5, 6.25, 3.125 and 1.5625 M of compounds. The plates were then further incubated for 72h. Cell viability was determined using 3-(4,5-dimethylthiazole-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Results: Incubation of liver cells with all 3 derivatives showed a dose-dependent reduction in cell viability for both THLE-2 and HEPG2 cells. However, HEPG2 cells were more viable than THLE-2 cells. All 3 derivatives moderately cytotoxic to THLE-2 cells when compared to HEP-G2 cells. Interestingly, Ibuprofen (2MPPPA) was the least cytotoxic. Conclusion: This study has proven the safety of ibuprofen as an OTC (Over the counter) NSAID which is one of the most popular NSAID worldwide. Therefore, these results provided the safety and data for future studies of propionic acid NSAIDs’ efficacy and toxicity studies.